6x-4=3-(x-+5)

Simple and best practice solution for 6x-4=3-(x-+5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x-4=3-(x-+5) equation:



6x-4=3-(x-+5)
We move all terms to the left:
6x-4-(3-(x-+5))=0
We add all the numbers together, and all the variables
6x-(3-(+x))-4=0
We calculate terms in parentheses: -(3-(+x)), so:
3-(+x)
determiningTheFunctionDomain -(+x)+3
We get rid of parentheses
-x+3
We add all the numbers together, and all the variables
-1x+3
Back to the equation:
-(-1x+3)
We get rid of parentheses
6x+1x-3-4=0
We add all the numbers together, and all the variables
7x-7=0
We move all terms containing x to the left, all other terms to the right
7x=7
x=7/7
x=1

See similar equations:

| y=-10-2(2) | | 4*x=8x | | x/4+2x/5-1/2=2 | | -3c−5=-2c | | 1+3n=-4n+8 | | n+-10.8=-34.4 | | 3d=-20+5d | | 10•c-8=90 | | 5+14a=9−5 | | w/3+6=-8 | | b-17+12=4b-68 | | 3x(-10-2x)=0 | | x+6/7=+6 | | 3(x-5)=353x-5=35 | | x-19.4=14.1 | | 4b-17+12=b | | 0.06=x-1.95x | | 29-8x=x+5 | | 16+3b=b | | (5x+2)=6x | | 11y+6=86 | | 6x7=30+ | | 81=4r+5r | | 7c-3+2c=33 | | 60+n=114 | | 60+n=144 | | 10x-3x+x-2=14 | | 5n+18=+n | | 10f+2=8f+4 | | 10t+-13t−-14t+-1=10 | | 72=(-3t)-(-5t) | | 9(x-9)-3=-5(2x+4) |

Equations solver categories